Concrete Delamination Analysis and Repair Methods in Residential Buildings - Reynold Andika Pratama; Yuli Sulistyohadi; Jody Sutiawan; Pangeran Holong Sitorus (Asosiasi Dosen Muda Indonesia, 2025)
Laminated concrete involves removing a thin layer from the concrete surface, making it prone to abrasion and weakening the structure. This delamination, often termed concrete weathering, produces a